Characterizing deformation behaviour of an oxidized high speed steel: Effects of nanoindentation depth, friction and oxide scale porosity. (May 2019) - Deng, G.Y.; Tieu, A.K.; Su, L.H.; Zhu, H.T.; Zhu, Q.; Zamri, W.F.H.; Kong, C.
Highlights: This study provides the first systematic evaluation on nanoindentation deformation behaviour on an oxidized HSS surface by both experiment and modelling. A finite element model considering practical microstructural features (thickness and porosity) of oxide scale has been developed and verified by experimental results. Obvious nanoindentation size effect was observed and three regions can be distinguished based on the maximum nanoindentation depth. Friction has only a slight influence during nanoindentation, but porosity in oxide scale has a great effect. Abstract: In the present paper, a systematic study on the deformation behaviour of an oxidized high speed steel (HSS) during nanoindentation has been conducted. Specimens cut from a HSS work roll were oxidized first to develop the oxide layer with thickness close to that built up on a HSS work roll surface during hot rolling in industry. Then, nanoindentation tests with three typical peak loads from low to high (namely 2 mN, 20 mN, and 200 mN) were conducted on the oxide scale surface. Porosity in oxide scale and its surface morphology features were examined by transmission electron microscopy (TEM) and scanning electron microscopy (SEM), respectively. In addition, a finite element model was developed and verified by comparing with the experimental measured load-depth curves. With the developed model, for the first time, a systematic investigation has been done to understand the effects of nanoindentation depth (from 10 nm to 1250 nm), friction coefficient (from 0 to 0.6) and initial porosity of oxide scale (from 0 to 20%) during nanoindentation on the deformation behaviours of both oxide scale and HSS substrate. It has been found an obvious size effect and three regions can be divided according to nanoindentation depth, based on the evolution of mechanical property, porosity in oxide scale, and plastic deformations in both oxide scale and HSS substrate. This study also revealed that friction has a slight influence during nanoindentation and almost the same results were obtained when the friction coefficient is larger than 0.3. By contrast, a large influence of porosity in oxide scale was observed. Graphical abstract: Image, graphical abstract